2013
DOI: 10.1039/c2ce26388b
|View full text |Cite
|
Sign up to set email alerts
|

Structural variety of 5-fluoroarene-2-aminopyrimidine in comparison to 2-aminopyrimidine silver(i) coordination polymers: progress report and overview

Abstract: A variety of fluoroarene-2-aminopyrimidine (FAP) silver(I) coordination polymers (CPs) has been synthesized based on newly synthesized FAP derivatives, namely 5-(p-methoxytetrafluorophenyl)-2aminopyrimidine (OFAP) and 5-(p-dimethylaminotetrafluorophenyl)-2-aminopyrimidine (NFAP), and different counterions (OTf 2 , TFA 2 , ClO 4 2 , NO 3 2). Their solid-state assembly as well as optical properties in terms of luminescence and infrared (IR) spectroscopy were investigated. Out of the several structures described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…The LIDT is estimated to be 681 MW cm −2 at 1064 nm, which is approximately 1.7 times greater than that of KDP (406 MW cm −2 ) and comparable to that of 4HPP (882 MW cm −2 at 1064 nm). 7 As shown in Figure 5, the 2APP crystal also emits a purple fluorescence centered at 382 nm, which is ascribed to the π → π* and n → π* transitions, 23,24 which are similar to those of the related 2AP derivatives, such as 5-pentafluorophenyl-2aminopyrimidine (FAP) (λ em = 387 nm), 23 5-(p-methoxytetrafluorophenyl)-2-aminopyrimidine (OFAP) (λ em = 376 nm), 23 5-(p-dimethylaminotetrafluorophenyl)-2-aminopyrimidine (NFAP) (λ em = 395 nm), 23 and 2-amino-4-phenyl-6methylpyrimidine (L) (λ em = 375 nm). 24 More remarkably, the fluorescence quantum yield of the 2APP solid (Φ = 30.6%) is much higher than those of the 2AP solid and its derivatives, such as 2AP (Φ = 0.075%), 23,25 2-amino-4-phenyl-6m e t h y l p y r i m i d i n e ( L ) ( Φ = 9 .…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The LIDT is estimated to be 681 MW cm −2 at 1064 nm, which is approximately 1.7 times greater than that of KDP (406 MW cm −2 ) and comparable to that of 4HPP (882 MW cm −2 at 1064 nm). 7 As shown in Figure 5, the 2APP crystal also emits a purple fluorescence centered at 382 nm, which is ascribed to the π → π* and n → π* transitions, 23,24 which are similar to those of the related 2AP derivatives, such as 5-pentafluorophenyl-2aminopyrimidine (FAP) (λ em = 387 nm), 23 5-(p-methoxytetrafluorophenyl)-2-aminopyrimidine (OFAP) (λ em = 376 nm), 23 5-(p-dimethylaminotetrafluorophenyl)-2-aminopyrimidine (NFAP) (λ em = 395 nm), 23 and 2-amino-4-phenyl-6methylpyrimidine (L) (λ em = 375 nm). 24 More remarkably, the fluorescence quantum yield of the 2APP solid (Φ = 30.6%) is much higher than those of the 2AP solid and its derivatives, such as 2AP (Φ = 0.075%), 23,25 2-amino-4-phenyl-6m e t h y l p y r i m i d i n e ( L ) ( Φ = 9 .…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Mattay's group used 5-polyfluoroarene-2-aminopyrimidine as a ligand to obtain a series of 1D AgIJI) coordination polymers with different counteranions (26-30 and 59-62). 40,50 Compound 26 showed double-strands bridged by an μ 2 -O:O′ ClO 4…”
Section: D Coordination Chainmentioning
confidence: 99%
“…Mattay's group showed that the polyfluoroarene-2-aminopyrimidine also could be used to obtain a series of 2D AgIJI) coordination layers modulated by anions (76-79). 40 In the chain of 76, the fluoroarene tail points to the same direction and forms weak π⋯π interaction (centroid distance: 3.70 Å) 62 with fluoroarene of the adjacent chain. In 77, the fluoroarene tail arranges toward the same direction, giving parallel alignment of the ligands.…”
Section: D Layermentioning
confidence: 99%
“…19 The ability of 2Apy and its functionalized compounds to form molecular architectures via strong intermolecular hydrogen bonds and p-p interactions make them suitable for designing supramolecular architectures. [20][21][22][23][24] The present work is devoted to the study of the reactions of cOH with 2Apy in aqueous medium using pulse radiolysis with optical absorption detection. A trustworthy computational protocol by one author of this article and his co-worker 25 designed recently for getting the accurate kinetic data for radical-molecule reactions in solution have been applied for identifying appropriate mechanism (from RAF, SET, and HT) operated in the experiment.…”
Section: Introductionmentioning
confidence: 99%